Agrowaste bioconversion and microbial fortification have prospects for soil health, crop productivity, and eco-enterprising - Dhananjaya P. Singh; Ratna Prabha; Shukla Renu; Pramod Kumar Sahu; Vivek Singh (International Journal of Recycling of Organic Waste in Agriculture, 2019)
Abstract Purpose Agricultural chemicals either used as nutrient inputs for soil fertility or pesticides are creating physicochemical and biological deterioration of the soils and disturbing the agro-ecosystems worldwide. Alarming concerns towards integrated agroecology demand for renewed interest in low-external input-based farming practices. These practices comprise strengthening of soil biological properties, recycling of inherent soil minerals and reuse of agricultural residual wastes. Methods We described approaches for the bioconversion of agricultural residual wastes into value-added compost. The process involves conversion of residual waste into raw compost followed by its fortification with beneficial decomposer microorganisms to produce quality fortified compost product. Finally, incubation of fortified compost with single or consortia of beneficial microorganisms like N-fixers, P-solubilizers or K-mobilizers and biocontrol agents further enriches compost to produce bioorganic products. Results Bioconversion of agricultural wastes into compost using potential decomposer microorganisms and fortification of decomposed organic matter with beneficial bacterial and fungal species is of immense importance. Additional enrichment of compost with botanicals, humic acid, amino acids, mineral nutrients, phytohormones etc. may also add value to the bioinput products. Conclusion In an integrated way, on-farm production of raw compost using different agricultural residual wastes and its further fortification with bioorganic farm inputs can help farmers produce value-added compost products for direct application in the crop production. Adoption of microbial bioconversion technologies and their field applications may become eco-enterprising for the rural resource-poor farming communities for enhancing their livelihood along with improving farm productivity and soil health.